Freedom and belief - Strawson, Galen (Oxford Oxford university press, 1986)
This is a revised and updated edition of Galen Strawson's groundbreaking first book, where he argues that there is a fundamental sense in which there is no such thing as free will or true moral responsibility (as this is ordinarily understood). This conclusion is very hard to accept. On the whole we continue to believe firmly both that we have free will and that we are truly morally responsible for what we do. Strawson devotes much of the book to an attempt to explain why this is so. He examines various aspects of the 'cognitive phenomenology' of freedom - the nature, causes, and consequences of our deep commitment to belief in freedom. In particular, he considers at length a number of problems that are raised by the suggestion that, if freedom were possible, believing oneself to be a free agent would be a necessary condition of being a free agent.